Extending Leadership behavior & Strategic skills for managers to handle Business Continuity and Disaster Management in Small and Medium Sized Enterprises (SMEs) - Somashekar Bukahally, Lankesh (Digital Repository of Theses, 2025)
The increasing complexity of modern business environments demands the enhancement of leadership behavior and strategic skills among managers, particularly in Small and Medium-Sized Enterprises (SMEs), to effectively handle business continuity and disaster management. SMEs are highly vulnerable to disruptions, making proactive leadership and robust strategies critical for resilience and sustainability. Purpose/Objective This study explores how extending leadership behavior and strategic decision-making skills equips managers to address challenges related to business continuity and disaster management in SMEs. The study aims to provide actionable insights for SME managers, policymakers, and industry stakeholders to build organizational resilience. Methodology/Approach Using a mixed-methods approach, this study combines a comprehensive review of literature, case studies, and insights from expert interviews. It examines key leadership behaviors, strategic planning frameworks, and best practices in disaster management tailored to the SME context. Findings/Results The findings indicate that adaptive leadership, effective communication, and scenariobased strategic planning significantly enhance SMEs' capacity to navigate crises. Barriers such as limited resources, insufficient training, and lack of disaster preparedness plans were identified, alongside opportunities for leveraging technology, collaboration, and innovation to strengthen continuity practices. Significance/Implications This study underscores the pivotal role of leadership in fostering a culture of preparedness and resilience within SMEs. By adopting targeted strategies, managers can enhance operational stability, safeguard assets, and ensure long-term sustainability even in the face of disruptions. Conclusions The research highlights that extending leadership and strategic capabilities is essential for mitigating risks and ensuring business continuity in SMEs. A proactive and well-equipped leadership approach can drive resilience, minimize disruptions, and support sustainable growth. Limitations The study focuses on SMEs within specific industries and geographic regions, which may limit the generalizability of the findings. Further research is needed to explore cross-sectoral and global perspectives. Recommendations/Future Research Future studies should investigate the integration of emerging technologies like AI and data analytics into disaster management frameworks for SMEs. Longitudinal research on leadership development and its impact on organizational resilience can provide deeper insights into sustaining continuity under dynamic conditions.